Active vibration control using circular force generators - Swanson, D.; Black, P.; Girondin, V.; Bachmeyer, P.; Jolly, M. (My University, 2015)
LORD Corporation's Active Vibration Control Systems (AVCS) using Circular Force Generators (CFG) can provide significant improvements in vibration reduction, weight, power, and modularity over existing helicopter vibration control systems. The AVCS allows for a modular design approach both in hardware where a mixture of accelerometer types and CFG design variants can be used, as well as, in software where tuning of the system is done through the use of Parameter Data Item Files. CFGs allow for the production of diverse force shapes at a significantly lower weight than traditional linear force generators. The CFGs also require low power with significant reduction in power over a broad frequency range with good applicability for variable rotor speed helicopters. Laboratory based experiments show that AVC with circular force inputs can produce similar or improved vibratory reduction both in steady state and transient conditions.
Keywords: Dynamics